2007
DOI: 10.1007/s00428-007-0533-1
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma with concomitant adenocarcinoma arising in a Barrett’s oesophagus: report of a case with a favourable behaviour

Abstract: Most Barrett's oesophagus-associated cancers are adenocarcinomas which occur in a pure form. They are rarely combined with another type of malignancy, such as endocrine tumours. Within the endocrine spectrum, small cell carcinomas (SmCC) usually have a highly aggressive behaviour with a poor prognosis. We report a case of composite SmCC and adenocarcinoma in the setting of a Barrett's oesophagus, in a 54-year-old man. This tumour was identified on a surgical specimen after neoadjuvant treatment with radiothera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 20 publications
0
12
0
2
Order By: Relevance
“…One reason for the coexistence of small cell carcinoma, squamous cell carcinoma and glandular elements in the same lesion is that small cells have the potential for further differentiation into either mucin-producing or keratin-forming cells [18]. Besides, SCCE can also arise in Barrett’s esophagus [19], [20]. Another viewpoint is that the SCCE’s origin is from neuroendocrine cells of the submucosal gland or stratum basal, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the coexistence of small cell carcinoma, squamous cell carcinoma and glandular elements in the same lesion is that small cells have the potential for further differentiation into either mucin-producing or keratin-forming cells [18]. Besides, SCCE can also arise in Barrett’s esophagus [19], [20]. Another viewpoint is that the SCCE’s origin is from neuroendocrine cells of the submucosal gland or stratum basal, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Because the histological and clinical characteristics of SmCCE closely resemble those of small cell carcinoma of the lung, combined therapy is often used, such as VP16/cisplatin [8] or CPT11/cisplatin therapy [12]. The treatment of SmCCE has also been reported to consist of 5-FU/cisplatin therapy according to the conventional chemotherapy for SqCCE [13,14]. Yamashita et al [8] reported the efficacy of VP16/ cisplatin and radiotherapy, and its response rate was 77.8% (seven out of nine cases) in primary SmCCE.…”
Section: Discussionmentioning
confidence: 99%
“…4 After treatment, an upper gastrointestinal series (a) and endoscopy (b) showed no elevated lesion of the tumor, but instead an ulcerative lesion to be chosen in most cases [3,4,[7][8][9][10][11]. However, CPT11/ cisplatin, 5-FU, or some other therapy has also been selected recently [12][13][14]. These results indicated that no standard regimen for SmCCE has yet been established owing to the paucity of cases studied and the lack of any large studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,5,9,[14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The baseline characteristics of all patients are shown in Table 1. The characteristics of patients from our institution are summarized in Table 2.…”
mentioning
confidence: 99%